GENTAMICIN MODULATES THE GENE EXPRESSION OF HLA IN METHICILLIN RESISTANCE STAPHYLOCOCCUS AUREUS BIOFILM - Nihad Taha Mohammed Jaddoa; Harith Jabbar Fahad Al-Mathkhury (Journal of Global Pharma Technology, 2018)
Objective: The present work was undertaken to investigate the impact of sub inhibitory concentration of gentamicin on hla gene expression in methicillin resistant Staphylococcus aureus isolates. Methods: The bacterial isolates used in this study represent 33 MRSA strains, previously isolated form patients visiting several hospitals in Baghdad. Gentamicin, vancomycin, and oxacillin MIC were determined using broth dilution method. Microtiter plate method was adopted to investigate the biofilm forming capacity. Alpha hemolysin was detected by culturing MRSA isolates on rabbit blood agar. Furthermore, hla gene was detected in MRSA isolates using conventional PCR technique; while, qRT-PCR method was performed to assay the hla expression in planktonic and biofilm cells in presence and absence of gentamicin. Results: the present results demonstrated that 12 (36.36%) isolates were gentamicin-resistant; whereas, all isolates were resistant to oxacillin and sensitive to vancomycin. Out of 33 MRSA, 3, 23, and 7 isolates formed a weak, moderate, and strong biofilm, respectively. Phenotypically, 30 isolates produced alpha hemolysin on rabbit blood agar plates; nevertheless, hla gene was located in 29 isolates. Of considerable interest, the addition of gentamicin significantly (P < 0.05) reduced the hemolysis activity; while, insignificant fold change (less than two) of hla gene was observed in all tested isolates in the presence of sub MIC of gentamicin (16 µg/ml). Conclusion: gentamicin upregulated the hla gene expression in biofilm cells; hitherto, this increment was isolate specific.